Proposed Training Program on Competency Needs and Challenges of Inclusion Assistants in Abu Dhabi - Collorado, Chrizza Mae Gura (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigated the competency needs and challenges faced by Inclusion Assistants (IAs) supporting Students of Determination (SODs) in Abu Dhabi schools to inform the development of a tailored training program. Using a concurrent triangulation mixed-methods design, data were collected via surveys and interviews from 100 IAs. Findings indicate most IAs (aged 26–29) lack formal training and advanced qualifications. Competency was rated highest in disability understanding (3.86), lesson plan modification (3.81), and empathy (3.83), but collaboration with teachers (2.84), communication (3.08), and assistive technology use (3.04–3.26) require improvement. Key professional development barriers include irrelevant content (3.91), poor applicability (3.93), and limited access (3.83). The study highlights the need for a context-specific training program to enhance collaboration, emotional intelligence, and technological skills, aiming to empower IAs and improve inclusive education outcomes for SODs in Abu Dhabi.